Neonate with VACTERL Association and a Branchial Arch Anomaly without Hydrocephalus - Danitza Velazquez; Elaine Pereira; Thomas Havranek (Thieme Medical Publishers, Inc., 2016)
Abstract VACTERL (vertebral anomalies, anal atresia, cardiac defect, tracheoesophageal fistula, renal anomaly, limb anomalies) is an association of anomalies with a wide spectrum of phenotypic expression. While the majority of cases are sporadic, there is evidence of an inherited component in a small number of patients as well as the potential influence of nongenetic risk factors (maternal diabetes mellitus). Presence of hydrocephalus has been reported in VACTERL patients (VACTERL-H) in the past, with some displaying branchial arch anomalies. We report the unique case of an infant of diabetic mother with VACTERL association and a branchial arch anomaly-in the absence of hydrocephalus.